The Effect of National Culture on Leverage Decisions in Emerging Markets - felicia julianti; Sung Suk Kim (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2022)
This research investigates whether cultural variables explain diversity in corporate leverage in developing markets. Adaption in government borrowing, as well as macroeconomic uncertainty and financial sector expansion, play a larger effect. Individualism is highly positive connected with leverage except for short-term debt, while uncertainty-avoidance is negatively correlated with leverage except for long-term debt. We also investigate the buildup and dissipation of leverage by studying the relationship between company profitability, size, market to book, R&D, which all negatively connected while tangible assets remain positively related.